2019
DOI: 10.1111/jcmm.14293
|View full text |Cite
|
Sign up to set email alerts
|

Aucubin inhibited lipid accumulation and oxidative stress via Nrf2/HO‐1 and AMPK signalling pathways

Abstract: Aucubin ( AU ) is the main active ingredient of Aucuba japonica which has showed many positive effects such as anti‐inflammation and liver protection. Non‐alcoholic fatty liver disease ( NAFLD ) is the most common cause of chronic liver disease. In this research, we explored the effects of AU on the tyloxapol‐induced NAFLD in mice and apolipoprotein C‐ III (apoC‐ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 48 publications
3
77
0
Order By: Relevance
“…However, under conditions of injury, Nrf2 dissociates from Keap1 and translocates into the nucleus, where it activates the Nrf2-ARE pathway. Au has been demonstrated to have the property to promote Nrf2 into nuclear, which triggers Nrf2-induced antioxidative signaling pathway [31,32]. In both in vitro and in vivo studies, we did nd that Au enhanced nuclear accumulation of Nrf2 and increased cytoplasmic expression of HO-1 and NQO1 in neurons.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…However, under conditions of injury, Nrf2 dissociates from Keap1 and translocates into the nucleus, where it activates the Nrf2-ARE pathway. Au has been demonstrated to have the property to promote Nrf2 into nuclear, which triggers Nrf2-induced antioxidative signaling pathway [31,32]. In both in vitro and in vivo studies, we did nd that Au enhanced nuclear accumulation of Nrf2 and increased cytoplasmic expression of HO-1 and NQO1 in neurons.…”
Section: Discussionmentioning
confidence: 69%
“…There are several potential limitations deserving attention in our experiments. First, although studies have shown that Au plays a protective role by phosphorylating AMPK to regulate Nrf2 translocation into the nucleus [31,32], we did not explore the speci c molecular mechanism in TBI mice. Second, we only used Nrf2 shRNA to explore the mechanism, which might not have had an e cient inhibitor effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Au has been demonstrated to have the property to promote Nrf2 into nuclear, which triggers Nrf2induced antioxidative signaling pathway [31,32]. In both in vitro and vivo studies, we did find that Au enhanced nuclear accumulation of Nrf2 and increased cytoplasmic expression of HO-1 and NQO1 in neurons.…”
Section: Discussionmentioning
confidence: 63%
“…Substantial evidence suggests that oxidative stress participates in secondary brain injury [4,10,11,17]. Recently, studies have demonstrated that Au has potent antioxidant effects and reduces excessive production of ROS in non-alcoholic fatty liver disease [31] and acute lung injury [32]. Until now, few experiments investigated the potential antioxidative in CNS diseases, except that Xue and colleagues reported the antioxidant bioactivities of Au in P12 cells (a neuronal cell line) [38,39] and in a rat model of diabetic encephalopathy [27][28][29].…”
Section: Discussionmentioning
confidence: 99%